The effect of religion on cooperation and altruistic punishment: Experimental evidence from public goods experiments - Alpaslan Akay; Gökhan Karabulut; Peter Martinsson (Institute for the Study of Labor (IZA), 2011)
This paper experimentally examines how religious festivals and the degree of religiosity affect cooperation and altruistic punishment by using public goods experiments. We conducted the experiments in Turkey at different points in time; one on the most religious day during Ramadan (the Night of Power - Laylat al-Qadr) and the other at a time without any religious festivals other than the normal daily prayers. The overall results show no differences in cooperation or altruistic punishment among individuals during Ramadan, even when the degree of their religiosity varied. However, less religious people did change their cooperative behaviour in response to religious festivals. Most of the differences can, however, be explained by differences in beliefs about others contributions. By and large, this indicates the importance of conditional cooperation.
urn:nbn:de:101:1-201201103108
Keywords: C72; C91; H41; 330; cooperation; experiment; public goods; punishment; religion; Religion; Nichtkooperatives Spiel; Kooperation; Öffentliches Gut; Altruismus; Test; Türkei